Low-Cost, Easy-to-Assemble Neonatal Procedural Trainers: Chest Tube, Pericardiocentesis, and Exchange Transfusion - Orna Rosen; Deborah Campbell; Christie Bruno; Larissa Gabelman; Dena Goffman; Robert Angert (Association of American Medical Colleges, 2014)
Abstract This resource presents three task-training models for critical neonatal intensive care procedures: chest tube insertion, exchange transfusion, and pericardiocentesis. Practicing in a simulated environment has many advantages when the procedure is rarely encountered and of a critical, high-risk nature. Commercially produced models for these procedures are either not available or are prohibitively expensive. The models described in this submission are constructed from simple materials and easily available products. They are realistic and simple enough to immerse the learner in the procedure, rather than distract them with complex technology. Each model is described in detail so that it can be recreated by users. All key aspects of the design, construction, and use of models are provided. Clear photographs of the models including details about the construction are included in the manuscript. We have used these models in a training program for neonatal fellows, pediatric residents, nurse practitioners, physician assistants, and medical students. Learners in our institution and simulation educators at an international simulation conference have used these models. They have reported increased confidence and have demonstrated mastery of the techniques in live scenarios. These models are intended to allow learners to practice their skills in a low risk environment. Learners are required to repeat the procedures until they feel confident and demonstrate mastery on objective skills assessment.